Contribution of Remittance in Economic Growth of Nepal (The Batuk, 2019)
This study paper intended to investigate how remittance income affected economic growth of Nepal. The main objectives of this study tries to find the answer on two questions: First, does the remittance inflow is contributing to the growth of an economy of Nepal? Second what is the trend of remittance inflow in Nepal over the year? We have used Unit Root Test, Ordinary Least Squared Regression Analysis, and Ratio Analysis Test. In this research, it is investigated that whether remittances have growth impact on Nepalese economy, by using data belong to 1990-2016 period. The time series regression findings show that remittance flow to Nepal have statistically meaningful and positive impact on GDP growth. This paper is based on the secondary source of information briefly explain the potentiality of remittance income for the GDP growth of Nepal.